OBSERVATION ON THE SEASONAL PRAWN FISHERY OF THE PERIATHALAI COAST IN THE GULF OF MANNAR - Rajamani, M; Manickaraja, M (Indian Journal of Fisheries, 2011)
The seasonal prawn fishery of Periathalai, a fishing village on the south-east coast of Tamil Nadu, lastsfor a period of three to four months in a year. The fishery was constituted exculsively by Penaeus indicus.During the three year period from 1985 to 1987 the estimated catch of P. indicus ranged between 95.9 and106.7 tonnes and the maximum catch was recorded in the month of July. There was a gradual decreasein the female population. Mature and spent-recovering females formed major portion whereas immaturefemales were seldom recorded in the catches